Identification of traditional medicinal plant extracts with novel anti-influenza activity. - Dhivya Rajasekaran; Enzo A Palombo; Tiong Chia Yeo; Diana Lim Siok Ley; Chu Lee Tu; Francois Malherbe; Lara Grollo (PLoS ONE, 2013)
The emergence of drug resistant variants of the influenza virus has led to a need to identify novel and effective antiviral agents. As an alternative to synthetic drugs, the consolidation of empirical knowledge with ethnopharmacological evidence of medicinal plants offers a novel platform for the development of antiviral drugs. The aim of this study was to identify plant extracts with proven activity against the influenza virus. Extracts of fifty medicinal plants, originating from the tropical rainforests of Borneo used as herbal medicines by traditional healers to treat flu-like symptoms, were tested against the H1N1 and H3N1 subtypes of the virus. In the initial phase, in vitro micro-inhibition assays along with cytotoxicity screening were performed on MDCK cells. Most plant extracts were found to be minimally cytotoxic, indicating that the compounds linked to an ethnomedical framework were relatively innocuous, and eleven crude extracts exhibited viral inhibition against both the strains. All extracts inhibited the enzymatic activity of viral neuraminidase and four extracts were also shown to act through the hemagglutination inhibition (HI) pathway. Moreover, the samples that acted through both HI and neuraminidase inhibition (NI) evidenced more than 90% reduction in virus adsorption and penetration, thereby indicating potent action in the early stages of viral replication. Concurrent studies involving Receptor Destroying Enzyme treatments of HI extracts indicated the presence of sialic acid-like component(s) that could be responsible for hemagglutination inhibition. The manifestation of both modes of viral inhibition in a single extract suggests that there may be a synergistic effect implicating more than one active component. Overall, our results provide substantive support for the use of Borneo traditional plants as promising sources of novel anti-influenza drug candidates. Furthermore, the pathways involving inhibition of hemagglutination could be a solution to the global occurrence of viral strains resistant to neuraminidase drugs.